Glucose isomerization catalyzed by bone char and the selective production of 5-hydroxymethylfurfural in aqueous media - Matsagar, Babasaheb M.; Van Nguyen, Chi; Hossain, Md. Shahriar A.; Islam, Md. Tofazzal; Yamauchi, Yusuke; Dhepe, Paresh L.; Wu, Kevin C. -W. (Sustainable Energy & Fuels, 2018)
The selective production of 5-hydroxymethylfurfural (HMF) is important, and it is difficult with glucose substrates in a water solvent. Here we demonstrate a selective method for glucose-to-HMF conversion using the combined catalysis of bone char and 1-methyl-3-(3-sulfopropyl)-imidazolium hydrogen sulfate acidic ionic liquid catalysts with a high HMF selectivity (54%) in water.